2018
DOI: 10.1111/jpc.14071
|View full text |Cite
|
Sign up to set email alerts
|

Emergency department presentations of febrile children to an Australian public hospital

Abstract: To our knowledge, this is the first Australian study that has assessed the impact of unspecified childhood fever on an Australian ED. Further investigation of presentations classified as potentially avoidable is warranted to investigate whether these could be managed in the primary care setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…Similar results were seen in various studies done in the Western world on febrile children presenting to the ED which showed pneumonia (43.7%) as most common cause of fever in <13 years old febrile children, and others being diarrhoea (17.3%) and cellulitis/adenitis (13%). [30][31][32] Finkelstein, et al reported similar findings in 3-36 months old infants in the US. 5 Studies done in Indian children also showed respiratory and the gastrointestinal illnesses as the most common diagnosis in febrile children.…”
Section: Discussionmentioning
confidence: 62%
“…Similar results were seen in various studies done in the Western world on febrile children presenting to the ED which showed pneumonia (43.7%) as most common cause of fever in <13 years old febrile children, and others being diarrhoea (17.3%) and cellulitis/adenitis (13%). [30][31][32] Finkelstein, et al reported similar findings in 3-36 months old infants in the US. 5 Studies done in Indian children also showed respiratory and the gastrointestinal illnesses as the most common diagnosis in febrile children.…”
Section: Discussionmentioning
confidence: 62%
“…Also, parents who usually sought help within the first 24 hours of the onset of febrile illness were used to giving antipyretics at a lower body temperature than those who believed that a consultation by a healthcare specialist could be delayed until later. Fever is one of the main reasons for seeking healthcare specialists after hours [19,21], despite the fact that many of these consultations are nonurgent and should be managed in primary care.…”
Section: Discussionmentioning
confidence: 99%
“…As most febrile episodes in children are benign, assessment in primary care and recommendations given by a family doctor or general practitioner should largely be sufficient for management. However, fever remains one of the main reasons for nonurgent visits to out-of-hours healthcare and pediatric emergency departments [5,16,17,18,19,20]. It is also the most common reason for use of medication in children [15,21,22,23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A logistic regression model was used to explore the relationship between the different clinical and biochemical variables and the decision to admit or discharge a febrile child. Demographic and clinical variables were included in the model based on data from previous studies 16,17 or if they reached a level of significance of p = 0.1 in the univariate analysis. The level of significance for all tests was set at p = 0.05.…”
Section: Methodsmentioning
confidence: 99%